Regional Policy of European Union in Spain and Portugal in 21st Century: Problems and Prospects - E. O. Zudova (Научный диалог, 2017)
The main aspects and directions of the regional policy of the European Union in the countries of the Iberian Peninsula (Spain and Portugal) in the beginning of the 21st century are examined. The author analyses the socio-economic development of territories, explores the condition of such areas as environmental protection, culture and innovations support, development of international relations with countries and regions of the Middle East and North Africa in the framework of the neighbourhood policy. The problem of the effectiveness of the implementation of regional programmes in Spain and Portugal is raised. The programmes “Madeira - Azores - Canary Islands,” “INTERREG MED,” “Southwestern Europe,” “Programme of Cross-border Cooperation in the Mediterranean Basin” are characterized. The success of regional cooperation in this area is assessed. Projects and initiatives implemented by the European Union in the Spanish and Portuguese regions are listed: project for the development of Porto-Gondomar, project “CypFire,” project “MedPAN,” projects “МЕЕТ: the Mediterranean experience of ecotourism” and “SLOWMED: “slow” food as a means of dialogue in Mediterranean contexts.” Their impact on the socio-economic development of the area is analysed. It is concluded that Spanish and Portuguese regions are interested in achieving results within the framework of regional policy implementation and the strengthening of relations in the context of European integration.